What is the status of immunotherapy in thyroid neoplasms? - Garcia-Alvarez, Alejandro; Hernando, Jorge; Carmona-Alonso, Ana; Capdevila, Jaume (Frontiers in Endocrinology, 2022)
Immunotherapy has changed the treatment of patients with advanced cancer, with different phase III trials showing durable responses across different histologies. This review focuses on the preclinical and clinical evidence of potential predictive biomarkers of response and efficacy of immunotherapy in thyroid neoplasms. PD-L1 staining by immunohistochemistry has shown higher expression in anaplastic thyroid cancer (ATC) compared to other subtypes. Tumor mutational burden in thyroid neoplasms is low, but seems to be higher again in ATC. Immune infiltrate at the tumor microenvironment (TME) differ between the different thyroid neoplasms’ subtypes. In general, differentiated thyroid cancer (DTC) have higher number of tumor-associated lymphocytes and Tregs, while ATC and medullary thyroid cancer (MTC) display a high density of tumor associated macrophages (TAMs). Nevertheless, results from clinical trials with immunotherapy as monotherapy o combinations have shown limited efficacy. Further investigation into new strategies aside from anti-CTLA-4/PD-1/PD-L1 antibodies, validation of predictive biomarkers and better population selection for clinical trials in thyroid neoplasms are more than needed in the near future.